Asperterpenes A and B, two unprecedented meroterpenoids from Aspergillus terreus with BACE1 inhibitory activities. Issue 10 (15th July 2016) - Qi, Changxing; Bao, Jian; Wang, Jianping; Zhu, Hucheng; Xue, Yongbo; Wang, Xiaochuan; Li, Hua; Sun, Weiguang; Gao, Weixi; Lai, Yongji; Chen, Jian-Guo; Zhang, Yonghui
Abstract : Asperterpenes A and B, two BACE1 inhibitors with unprecedented carbon skeletons isolated from Aspergillus terreus, exhibit potent anti-Alzheimer's disease activity. Abstract : Asperterpenes A (1 ) and B (2 ), two 3, 5-dimethylorsellinic acid-based meroterpenoids that contain a unique β-oriented Me-21 with an unprecedented 1, 2, 5-trimethyl-4, 9-dioxobicyclo[3.3.1]non-2-ene-3-carboxylic acid moiety, were obtained from Aspergillus terreus in very limited amounts of 3.6 mg and 1.8 mg, respectively. The absolute structure of1 was determined using X-ray diffraction. Because of the low yield of1, a comprehensive characterization of the BACE1 inhibitory activities of1 was completed via molecular biological, cell and animal studies guided by in silico target confirmation (ISTC). ISTC assays suggested that compounds1 and2 might be BACE1 inhibitors. In cell-based tests, asperterpenes A and B, as natural products, exhibited promising inhibitory activities against BACE1, with IC50 values of 78 and 59 nM, respectively. LY2811376 (the positive control), one of the most potent clinical BACE1 inhibitors, has shown an IC50 value of 260 nM. In vivo, compound1 exhibited activity similar to that of LY2811376 against Alzheimer's disease (AD) in 3xTg AD mice. Taken together, these findings demonstrate that asperterpene A, which contains a novel carbon skeleton, is the first terpenoid to exhibit effective BACE1 inhibitory activity. Moreover, 1 represents a potential lead compound and a versatile scaffold for the development of drugs for the treatment of AD.